All in eaudiobook - Matthews, Bella (Kings of Kroydon Hills, 2021)
Nothing prepared me for meeting Brady Ryan. I've been called football royalty my entire life. Born into a family that has experienced the highs and lows of the game. Constantly surrounded by football players and coaches. Now I'm following my father across the country for yet another team. I'm supposed to be spending this year finding myself, but can I do that with Brady by my side, or is he just another player? Natalie Sinclair came into my world and changed my life. Her father was the new professional coach in town, and her twin brother played on my team. This tiny dancer fit into our circle of friends like she was the missing piece. Neither of us might have been looking for something serious, but that changed the day we met. Now nothing can keep her from me. Not her twin brother. Not the threats of a jealous ex. Not even myself. Now I just need to convince her. She's it for me. She's the end game. I'm all in.